Ensaios farmacológicos clínicos de fases I e II com o hidrogel obtido a partir do extrato etanólico bruto da casca de Anacardium occidentale Linn. no tratamento da acne vulgar. - Sobral Filho, Jader Freire (2010)
The acne vulgaris is the most prevalent dermatologic disease of teen age. Many drugs are used in the treatment of acne but it is necessary a drug with safety and efficacy. The gel extracted from the bark Anacardium occidentale Linn. is indicated for topical treatment of inflammatory diseases. The purpose of this study was to evaluate the clinical pharmacology of this formulation in healthy volunteers. For this, a non-randomized open clinical trial was conducted with 40 healthy volunteers (22 female and 18 male), who administered the topical gel in their faces during 3 weeks. The volunteers were included in the study only when considered healthy after clinical assessment, physical examination and laboratory tests which preceded the study. The laboratory tests included: hematological, biochemical and serological analysis. The clinical and laboratory evaluation were repeated after the first week and at the end of the third week after the last administration. This gel was well tolerated by the 40 volunteers, and it has showed no adverse events. The clinical and laboratory data assessed before, during and after the test showed no signals of toxicity in various organs and systems evaluated, confirming the safety of the preparation for use in trials of therapeutic efficacy. A randomized, investigator-blinded, controlled study was conducted to evaluate the efficacy and safety of gel obtained from the bark of Anacardium occidentale Linn. (AO) versus adapalene gel 0,1%. Subjects were assigned randomly to receive either adapaleno gel 0,1% or AO once daily for 12 weeks. A total of 43 subjects with mild to moderate acne vulgaris (AV) were enrolled. Adapalene gel 0,1% was significantly superior to AO in noninflammatory lesion counts (p<0,005). But, the efficacy was statistically similar between two group for inflammatory lesion counts and in the reduction of total lesion count (p<1,0). Treatment-related adverse events were mostly mild-to-moderate in the group of adapaleno gel 0,1%. But in the group of AO no adverse events was seen. The results of this study show that Adapalene 0,1% gel was superior to AO in noninflammatory lesions of AV but similar in inflammatory and total counts lesions while AO was superior in safety and tolerability profile to adapaleno 0,1% gel.